Crowdsourcing in sustainable retail: A theoretical framework of success criteria - Peter Konhäusner (Journal of Risk and Financial Management, 2021)
Current research about crowdsourcing covers industries like food systems or logistics, leaving out the possible impact of crowdsourcing on sustainable retail. The debate about the sustainable impact of different industries is ongoing, especially discussing the adaption to the Sustainable Development Goals of the United Nations critically. This paper examines the influence of crowdsourcing on the sustainable aspects of retailing by applying a theoretical derivation as well as an empirical observation. After theoretically discussing the linkage between crowdfunding as a crowdsourcing category and sustainable retail utilizing a literature review, a theoretical framework employing the grounded theory approach is constructed. A total of 24 crowdfunding campaigns aiming at the market introduction of new products or services, each worth over 5 million USD funding volume and run on international crowdfunding platforms, have been taken into consideration. The outcome of the analysis is a theoretical framework presenting three different categories, in which successful crowdfunding campaigns impacting sustainable retail excel: sustainable economic behavior, sustainable community management and sustainable market adaptation. The derived model contributes to the theoretical discussion about the impact of crowdfunding and assists practitioners in reflecting about their approach and goal setting prior to and while crowdfunding.
Keywords: 330; crowdfunding; crowdsourcing; grounded theory; retail; sustainability; sustainable development goals (SDGs)